The Least Number of Intersection Points in Currency Fluctuation and Well- Approximating Line Graph under Constraints of the Elliott Wave Principle - Naoyasu Kita; Taisei Matsukuma (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2018)
Recently producing profit by exchanging currency of one country with that of the other has been conducted among traders. This activity is called â€œFXâ€ â€“ the abbreviation of Foreign eXchange. The fluctuation of the price of currency is caused by the psychology of traders so that it apparently varies at random. However, after so many traders take part in FX, the trend of currency expectedly shows several patterns and is said to be subject to a certain principle which was firstly suggested by R.N.Elliott (1871-1948). In our recent research, we have tried to construct an algorithm relying on this Elliott wave principle and establish an automated transaction of FX by a computer. One of the aims of this PC-algorithm is to determine the line graph which well-approximates a real currency fluctuation under the constraints of the Elliott principle. In this paper, we will survey how to construct an algorithm for well-approximating line graph, and theoretically discuss the least number of intersection points in currency fluctuation and the well-approximating line graph, which enhances the validity of the algorithm.